Love and Happiness - Paxton Thom . (Colorado Ski Areas . A.D.D. Video Productions, 2004)
These boys are shredding at Loveland, A-Basin, Copper Mt. Berthoud Pass and Mt Hood. All local kids from Clear Creek County.
A.D, D. Video
Bud Garcia, Corry Lollar, Bobby Murdock .
Colorado Ski Areas